PENGARUH SELF EFFICACY, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL LLOYD’S INN BALI DI SEMINYAK - Dewa Ayu Diah Arista; I Wayan Mendra; Ni Luh Gede Putu Purnawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Employee performance problems are known in the work quantity indicator, where there is a decrease in employee performance based on target data and the realization of room occupancy income in 2019 and 2020. Problems related to self-efficacy are known to have a lack of confidence in employees due to lack of expertise. Problems related to motivation, it is known that the rewards received by employees do not fulfill a sense of justice. Problems related to employee discipline are known to some employees who do not obey the SOP. This study aims to determine the effect of self-efficacy, motivation and work discipline on employee performance at the Lloyd's Inn Bali Hotel in Seminyak. This research was conducted at the Lloyd's Inn Bali Hotel using a population and a sample of 50 employees at the Lloyd's Inn Bali Hotel. The sampling technique used in this research is the saturated sampling method or the census method. Data was collected through observation, interviews, questionnaires and documentation. The data analysis technique used in this study is multiple linear regression analysis which is processed using SPSS software version 23. Based on the results of the analysis, this study shows that self-efficacy partially has a positive and significant effect on employee performance at Lloyd's Inn Bali Hotel. Motivation partially has a positive and significant effect on employee performance at the Lloyd's Inn Bali Hotel. Work discipline partially has a positive and significant effect on employee performance at the Lloyd's Inn Bali Hotel.